2023
DOI: 10.3390/vaccines11020401
|View full text |Cite
|
Sign up to set email alerts
|

Safety Monitoring of mRNA COVID-19 Vaccines in Children Aged 5 to 11 Years by Using EudraVigilance Pharmacovigilance Database: The CoVaxChild Study

Abstract: Although the safety profiles of mRNA COVID-19 vaccines (mRNA-1273 and BNT162b2) were evaluated in pre-authorization clinical trials, real-world data allow us to better define their benefit/risk ratio in the paediatric population. The current study aimed to evaluate the safety profiles of mRNA COVID-19 vaccines in children by analysing the pharmacovigilance data of the European spontaneous reporting system database EudraVigilance (EV) in the period from January 1st, 2021, to October 1st, 2022. During our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In line with this finding, Peter Yamoah et al reported that COVID-19 vaccine-induced AEFIs were more frequently observed in women than men and in patients of the age group 18-64 years [10]. Other studies reported similar difference in AEFIs distribution by gender [11,12].…”
Section: Discussionmentioning
confidence: 73%
“…In line with this finding, Peter Yamoah et al reported that COVID-19 vaccine-induced AEFIs were more frequently observed in women than men and in patients of the age group 18-64 years [10]. Other studies reported similar difference in AEFIs distribution by gender [11,12].…”
Section: Discussionmentioning
confidence: 73%
“…In this context, analysis of post-marketing data is particularly important as a source of new information that has not yet emerged, especially in specific populations [ 14 ]. In light of this, the aim of this study was a post-marketing evaluation of the safety profile of Zolgensma ® through the analysis of data retrieved from the European pharmacovigilance database Eudravigilance (EV).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, COVID-19 vaccines represent the best preventive strategy for protection from disease progression and poor clinical outcomes [ 5 , 6 ]. Various vaccine platforms have been used, including mRNA, non-replicating viral vector, protein subunit, and inactivated-virus-based vaccines [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%